A single-center retrospective comparison of muscle versus cutaneous free flaps for posterior elbow defect reconstruction - Falkner, Florian; Bigdeli, Amir Khosrow; Thomas, Benjamin; Panayi, Adriana; Mayer, Simon; Vollbach, Felix; Kneser, Ulrich; Gazyakan, Emre (Journal of plastic, reconstructive & aesthetic surgery, 2024)
Introduction - Comparative data on free flap outcomes for elbow defect reconstruction are still lacking. This study aimed to compare complication rates of free muscle flaps (MFs) versus cutaneous flaps (CFs) for posterior elbow reconstruction. - Methods - In a single-center retrospective analysis, patients who underwent posterior elbow reconstruction with free MFs and CFs from 2000 to 2021 were analyzed. Retrospective chart review included patient demographics, operative details, and post-operative complications. Outcomes of interest that were compared included microvascular complications, partial or total flap necroses, wound dehiscence, hematoma or flap infection, and donor-site complications. - Results - Sixty-six free flaps (CFs: n = 42; MFs: n = 24) were included, with a trend over time toward using CFs (64%). MFs were used for larger defects (CF: 175 ± 82 vs. MF: 212 ± 146 cm2; p = 0.13). Outcome analysis revealed an equal distribution of microvascular complications (10% vs. 13%; p = 0.7), partial flap necrosis (7% vs. 8%; p > 0.9), wound dehiscence (7% vs. 4%; p > 0.9), evacuation of hematoma (10% vs. 4%; p = 0.7), and infection (0% vs. 4%; p = 0.4). Total flap necrosis requiring additional flap surgery was necessary in one CF (2%) and in no MF (0%) (p > 0.9). - Conclusion - Surgical outcomes, flap necrosis rates, and microsurgical complications did not differ between CFs and MFs. Both flap types are safe and effective options. The free anterolateral thigh and latissimus dorsi flaps represent indispensable workhorses for the reconstruction of extensive elbow defects.